Subclinical thrombus formation in bioprosthetic pulmonary valve conduits. (15th April 2019) - Jewgenow, Philipp; Schneider, Heike; Bökenkamp, Regina; Hörer, Jürgen; Cleuziou, Julie; Foth, Rudi; Horke, Alexander Paul; Eicken, Andreas; Paul, Thomas; Sigler, Matthias
Abstract: Objectives: Bioprosthetic pulmonary valve conduits have been reported with an increased risk of endocarditis. Thrombus formation is considered as source of these serious and life-threatening infections. We reviewed a series of explanted valved pulmonary conduits for histological evidence for thrombus formation. Materials and methods: Explanted bioprosthetic pulmonary valves were fixed in formalin and embedded in paraffin or in methylmethacrylate. Standard staining as well as immunohistochemical staining techniques were applied. Native pulmonary valves of German domestic pigs served as controls. Results: 47 valved pulmonary conduits (Hancock n = 23, Homograft n = 7, Contegra n = 7, Melody n = 7, other n = 3) were analyzed histologically. Average time of implantation had been 63 months (6 to 342 months). Indications for explantation included significant obstruction (n = 45), regurgitation (n = 7), and/or endocarditis (n = 6). In 44/47 (93%) specimen, we found accumulation of thrombotic material at the basis of the semilunar valve sinus to a variable degree. 11 patients had been treated with antiplatelet agents, 2 had received anticoagulants at the time of explantation. There was no suspicion of thrombus formation clinically or echocardiographically prior to explantation in any of the patients. Control porcine pulmonary valves (n = 5) did not show any evidence of accumulation of thrombotic material. Conclusions: In a large series of explanted valved pulmonary conduits, formation of subclinical, mostly non-infectious thrombotic material was an almost ubiquitous finding. We speculate that high incidence of endocarditis in bioprosthetic valves may in part be explained by thrombus apposition at the basis of conduit valve sinus. Highlights: Histology reveals subclinical thrombus formation in bioprosthetic valves. Incidence of subclinical thrombus formation in bioprosthetic pulmonary valves is high. Aspirin does prevent formation of fibrin condensations at bioprosthetic valves.